Assessment of heavy metal pollution and spatial distribution in waterfalls of Chattogram district, Bangladesh: Implications for drinking and irrigation purposes - Abdur Rouf Azad; Md. Rezaul Karim; Md. Refat Jahan Rakib; Md. Ripaj Uddin (Environmental Advances)
This study assesses the concentrations of heavy metals and their distribution as well as ecological status in the major waterfalls at Chattogram, namely Khoiyachora, Kupikatakhum, Napittachhara, Bagbiani, Sohosrodhara, and Suptadhara. The water from these waterfalls are being used by the local inhabitants for household, drinking and irrigation purposes. Eighteen water samples from six water waterfall were collected during the summer, rainy and winter seasons in 2022-2023. The concentrations of Na, K, Ca, Mg, Fe, Mn, Cu, Cd, Hg, Cr, and As in water samples were measured by Atomic Absorption Spectrometer (AAS), and compared with the national (ECR, 2023) and international standards (WHO, 2015). Heavy Metal Pollution Index (HPI) were calculated (18.51 to 22.87) showed below the critical limit of 100, indicating suitability for drinking. However, %Na (0.92) and the magnesium adsorption ratio (MAR) value (32.49) suggested that the water is unsuitable for irrigation but suitable for drinking. On the other hand, metrics such as the sodium adsorption ratio (SAR) (26.74) and Kelly's ratio (KR) (9.83) indicated suitability for irrigation. HPI values (0–25) indicate excellent water quality, safe for consumption. Heavy Metal Pollution Indices (HPIs) and multivariate statistical models (PCA, CA, and Pearson correlation) were applied to evaluate spatial-temporal variations, distribution, and pollution sources. CA grouped monitoring sites into two clusters based on anthropogenic and geo-genic inputs. PCA identified five significant principal components explaining 73.79 % of total variance. Seasonal and geographical variations in Mn, Fe, Cu, Cr, Cd, Pb, Zn, and As concentrations were observed, especially in northern and southern study areas, highlighting spatial differences in pollution patterns. The policymakers should take proper steps for monitor the waterfalls to ensure water security and environmental protection as well as water management for the nearby inhabitants.